2008
DOI: 10.1097/yic.0b013e328306a977
|View full text |Cite
|
Sign up to set email alerts
|

Association of the catechol-O-methyltransferase polymorphism with methylphenidate response in a classroom setting in children with attention-deficit hyperactivity disorder

Abstract: It has been postulated that the prefrontal cortex plays a key role in attention-deficit hyperactivity disorder (ADHD). The catechol-O-methyltransferase (COMT) enzyme degrades synaptic catecholamines and plays a specific role in the catabolism of prefrontal cortex dopamine. We investigated the association between the COMT valine (Val) 108/158 methionine (Met) polymorphism and the response to treatment with methylphenidate (MPH) in children with ADHD. This study included 124 children with ADHD in South Korea. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 43 publications
5
27
0
1
Order By: Relevance
“…Relevant to dopaminergic and noradrenergic transmission, we found support for earlier observations 19, 38, 39 that variants in COMT moderated clinical benefit from MPH. However, contrary to studies in healthy subjects 37 and typical ADHD, in our data set met -carriers showed a greater reduction in hyperactivity with MPH treatment than val/val homozygotes.…”
Section: Discussionsupporting
confidence: 88%
“…Relevant to dopaminergic and noradrenergic transmission, we found support for earlier observations 19, 38, 39 that variants in COMT moderated clinical benefit from MPH. However, contrary to studies in healthy subjects 37 and typical ADHD, in our data set met -carriers showed a greater reduction in hyperactivity with MPH treatment than val/val homozygotes.…”
Section: Discussionsupporting
confidence: 88%
“…In Caucasians, the Met allele was reported to be associated with better cognitive function (Bruder et al 2005;Aguilera et al 2008). Conversely, studies of East Asian samples indicated that the Val allele is associated with better cognitive function (Cheon et al 2008;Yeh et al 2009;Wang et al 2013). Considering the converse association findings of cognitive function mentioned above with COMT Val158Met in Caucasians and East Asians (Palmatier et al 1999) and the difference in the lifetime prevalence rate of MDD in Western vs. East Asian countries (Kessler et al 1994;Hwu et al 1996;Parker et al 2007), it is plausible to assume that the variant potentially involves MDD pathogenesis with ethnic differences, which may contribute to the inconsistency of previous findings.…”
Section: Introductionmentioning
confidence: 93%
“…A functional polymorphism at COMT’s codon 158 results in a single amino acid change (met for val) which changes enzyme activity levels. 39 Two of three studies have suggested a significant association between MPH effects on ADHD symptoms and this COMT polymorphism 20,25,40 (Cohen’s d effect sizes not available).…”
Section: Introductionmentioning
confidence: 99%